2009
DOI: 10.1161/circulationaha.109.854216
|View full text |Cite
|
Sign up to set email alerts
|

Preoperative Hemoglobin Level as a Predictor of Survival After Coronary Artery Bypass Grafting

Abstract: Background— The predictive value of the preoperative hemoglobin value after coronary artery bypass grafting (CABG) has not been well established. We studied how the preoperative hemoglobin level affects the survival of patients after CABG. Late mortality was compared with that of a general population. Methods and Results— Early and late mortality of all consecutive patients undergoing isolated CABG between Januar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

5
97
3
5

Year Published

2012
2012
2023
2023

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 158 publications
(119 citation statements)
references
References 17 publications
5
97
3
5
Order By: Relevance
“…59 Inappropriate transfusion practices may endanger patients and waste resources. A recent RCT demonstrated that a liberal transfusion strategy (a higher Hb threshold of 10 g dl 21 ) did not improve outcomes (death, inability to walk independently at a 60 day follow-up and in-hospital mordibity) compared with a restrictive strategy (Hb threshold of ,8 g dl 21 ), in a population of high-risk patients after hip-fracture surgery. 60 …”
Section: Transfusion and Preoperative Anaemiamentioning
confidence: 99%
See 4 more Smart Citations
“…59 Inappropriate transfusion practices may endanger patients and waste resources. A recent RCT demonstrated that a liberal transfusion strategy (a higher Hb threshold of 10 g dl 21 ) did not improve outcomes (death, inability to walk independently at a 60 day follow-up and in-hospital mordibity) compared with a restrictive strategy (Hb threshold of ,8 g dl 21 ), in a population of high-risk patients after hip-fracture surgery. 60 …”
Section: Transfusion and Preoperative Anaemiamentioning
confidence: 99%
“…11 12 A recent retrospective cohort study demonstrated a higher postoperative 30 day morbidity and mortality in patients who underwent major non-cardiac surgery with preoperative anaemia than in those without anaemia. 13 In elderly patients with hip fracture, anaemia (Hb ,12 g dl 21 for females and ,13 g dl 21 for males) was significantly associated with 2-to 5-and 3-fold increases in the multivariate-adjusted risk of 6 and 12 month mortality, respectively. 14 Patients with Hb ,10 g dl 21 were at a 5-fold increased risk of death.…”
mentioning
confidence: 98%
See 3 more Smart Citations